2007
DOI: 10.1038/ncb1534
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between β-catenin and HIF-1 promotes cellular adaptation to hypoxia

Abstract: Aberrant activation of beta-catenin promotes cell proliferation and initiates colorectal tumorigenesis. However, the expansion of tumours and the inadequacy of their local vasculature results in areas of hypoxia where cell growth is typically constrained. Here, we report a novel diversion in beta-catenin signalling triggered by hypoxia. We show that hypoxia inhibits beta-catenin-T-cell factor-4 (TCF-4) complex formation and transcriptional activity, resulting in a G1 arrest that involves the c-Myc-p21 axis. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
394
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 441 publications
(420 citation statements)
references
References 28 publications
22
394
4
Order By: Relevance
“…Our work implicates HIF1-a signalling as critically perturbed in FSHD and shows that HIF1A displays strong positive correlation with b-catenin in FSHD samples, providing mechanism for previous observations of involvement of downstream components of the HIF1-a pathway in FSHD [20]. HIF1-a binds b-catenin during hypoxia competitively with TCF-4 [43], which may both inhibit TCF4/b-catenindriven cell proliferation and increase transcription of hypoxic response genes, including VEGF. We found that in FSHD, correlation in gene expression between b-catenin, and both HIF1A and TCF-4, significantly increases, resulting in elevated angiogenic genes such as VEGF, providing an explanation for the hallmark oxidative stress sensitivity in FSHD, as well as retinal vasculature abnormalities [4,5].…”
Section: Discussionmentioning
confidence: 78%
“…Our work implicates HIF1-a signalling as critically perturbed in FSHD and shows that HIF1A displays strong positive correlation with b-catenin in FSHD samples, providing mechanism for previous observations of involvement of downstream components of the HIF1-a pathway in FSHD [20]. HIF1-a binds b-catenin during hypoxia competitively with TCF-4 [43], which may both inhibit TCF4/b-catenindriven cell proliferation and increase transcription of hypoxic response genes, including VEGF. We found that in FSHD, correlation in gene expression between b-catenin, and both HIF1A and TCF-4, significantly increases, resulting in elevated angiogenic genes such as VEGF, providing an explanation for the hallmark oxidative stress sensitivity in FSHD, as well as retinal vasculature abnormalities [4,5].…”
Section: Discussionmentioning
confidence: 78%
“…Perhaps HIF is regulated by oncogenes in addition to acting through the pathway regulated by hypoxia. For example, interactions of HIF1 with b-catenin in colon cancer cell lines have been reported (Kaidi et al, 2007). Also, it is possible that as both mature and immature vessels are being assessed, this may reflect effects of other growth factors and vascular differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia downregulates β-catenin (via its interaction with HIF-1α), which is stabilized in response to Wnt signalling and forms an active transcriptional complex with lymphoid enhancer factor/T-cell factor-4 (LEF/TCF4). Kaidi and colleagues demonstrated that HIF-1α competes with TCF4 for direct binding to β-catenin, resulting in hypoxia-mediated cell-cycle arrest and inhibition of transcriptional activity 74 . Intriguingly, β-catenin can also promote HIF-1α-mediated transcriptional activity, which might help cells to adapt to severe hypoxia 74.…”
Section: Hypoxia Modulates Wnt Activitymentioning
confidence: 99%